The Many Faces of Neuroendocrine Differentiation in Prostate Cancer Progression - Terry, Stephane; Beltran, Himisha (Frontiers in Oncology, 2014)
In normal prostate, neuroendocrine (NE) cells are rare and interspersed among the epithelium. These cells are believed to provide trophic signals to epithelial cell populations through the secretion of an abundance of neuropeptides that can diffuse to influence surrounding cells. In the setting of prostate cancer (PC), NE cells can also stimulate surrounding prostate adenocarcinoma cell growth, but in some cases adenocarcinoma cells themselves acquire NE characteristics. This epithelial plasticity is associated with decreased androgen receptor (AR) signaling and the accumulation of neuronal and stem cell characteristics. Transformation to a NE phenotype is one proposed mechanism of resistance to contemporary AR targeted treatments, is associated with poor prognosis, and thought to represent up to 25% of lethal PCs. Importantly, the advent of high-throughput technologies has started to provide clues for understanding the complex molecular profiles of tumors exhibiting NE differentiation. Here, we discuss these recent advances, the multifaceted manner by which a NE-like state may arise during the different stages of disease progression, and the potential benefit of this knowledge for the management of patients with advanced PC